Portfolio Manager Ownership and Mutual Fund Risk Taking - MA, Linlin (Institutional Knowledge at Singapore Management University, 2013)
This study examines the effects of portfolio manager ownership on the risk-taking behavior of mutual funds. Using both return-based and holding-based risk measures, we find that funds managed by portfolio managers with higher beneficial ownership exhibit lower risk. In particular, using holding-based risk-shifting measure and a difference-in-differences approach, we find that funds with higher managerial ownership adjust their portfolio holdings to a lower risk level. Further investigation shows that the reduction in total risk for funds with greater managerial ownership is driven by the drop in systematic risk. Interestingly, we find that funds with higher managerial ownership exhibit higher idiosyncratic risk, which is consistent with the idea that these managers employ non-conventional and specialized investment strategies. Moreover, funds with higher managerial ownership show superior subsequent risk-adjusted performance and attract more capital inflows. Overall, our results suggest that managerial ownership aligns portfolio managers’ interests with those of fund shareholders, which leads to a reduction in fund risk taking and superior risk-adjusted performance.